(untitled) (Jurnal Teknologi Industri Pertanian, 2026)
Lasem hand-drawn batik is an Indonesian cultural heritage characterized by motifs and colors resulting from the acculturation of Javanese and Chinese cultures. Currently, Lasem hand-drawn batik entrepreneurs have begun to utilize social media, especially Instagram, to reach a wider market. Batik Rumah Merah, which is the object of this study, has five Instagram accounts, with varying engagement rates. The performance of the five accounts needs to be monitored, so that Batik Rumah Merah can determine targets and plans for the next period. Thus, this study aims to design a decision support system for assessing the performance of Batik Rumah Merah’s Instagram accounts. The decision-making method used is the Weighted Sum Model (WSM). The research was carried out through several main steps, namely the preliminary stage, determining criteria, determining alternatives, data collection, designing a decision support system, designing a business process, analysis, and conclusions. The criteria used are followers growth rate, weekly followers, steady growth factor, weekly engagement rate, engagement rate, average likes, average comments, weekly posts, followers ratio, and comments ratio. The weights used can be determined by the user. The alternatives used are five Instagram accounts belonging to Batik Rumah Merah. The designed system is equipped with a business process, making it easier for users. The results obtained using the WSM method produced a value for rank 1 with a value of 0.59862, rank 2 with a value of 0.5491, rank 3 with a value of 0.4168, rank 4 with a value of 0.3464, rank 5 with a value of 0.3034 with the order rumahmerahindonesia, oemahbatik_nusantara, batikrumahmerahlasem, oemahbajulasem, oemahbatiklasem. Keyword: engagement rate, instagram, decision support system